Feeling Offended: A Blow to Our Image and Our Social Relationships - Poggi, Isabella; D’Errico, Francesca (Frontiers in Psychology, 2018)
The paper presents a survey study that investigates the self-conscious emotion of feeling offended and provides an account of it in terms of a socio-cognitive model of emotions. Based on the qualitative and quantitative analysis of the participants’ answers, the study provides a definition of offence and of the feeling of offence in terms of its “mental ingredients”, the beliefs and goals represented in a person who feels this emotion, and finds out what are its necessary and aggravating conditions, what are the explicit and implicit causes of offence (the other’s actions, omissions, inferred mental states), what negative evaluations are offensive and why. It also shows that the feeling of offense is not only triggered about honour or public image, but it is mainly felt in personal affective relationships like. The paper finally highlights that high self-esteem may protect a person against the feeling of offence and the constellation of negative emotions triggered by it.